El acompañamiento familiar y su incidencia en la escolaridad de los niños con NEE de educación básica elemental y media de la Escuela Dr. Reinaldo Espinoza Aguilar, periodo 2021-2022 - Tandazo Núñez, Erika Stefania (2022)
The present research work titled: Family support and its incidence in the schooling of children with special educational needs (SEN) of elementary and middle basic education of the Dr. Reinaldo Espinoza Aguilar School, academic period 2021-2022, had as general objective to analyze family support and its incidence in the schooling of children with special educational needs (SEN) of elementary and middle basic education of the Dr. Reinaldo Espinoza Aguilar School, academic period 2021-2022. The research work has a mixed approach, it is descriptive and cross-sectional. The methods used were: the scientific method, deductive-inductive, analytical-synthetic and the bibliographic method. As a technique the survey and the semi-structured interview were used; the instrument was the questionnaire which was structured by 8 multiple-choice questions and 13 closed type questions for parents; and 8 closed type questions for teachers. The sample was non-probabilistic with a selection criterion for convenience. The study was carried out with 17 families of children with special educational needs (SEN) and 4 teachers responsible for elementary and middle school. The gotten results show that family support, among other incident factors, is characterized by the fact that 70% of parents sometimes control their children's schedules regarding their studies, 75% sometimes promote autonomy and responsibility; and, 75% of parents never participate in the parents' directives of the course, which is decisive in the child’s life and even more in their teaching process. It is concluded that the low participation and cooperation of parents both in school and in their children's homework, has consequences on their school failure, making the support, motivation and accompaniment of the family necessary, to promote adequate academic performance. Keywords: schooling, family support, special educational needs, academic performance.